Lions at the Gates: Trans-disciplinary Design of an Early Warning System to Improve Human-Lion Coexistence - Weise, Florian J.; Hauptmeier, Helmut; Stratford, Ken J.; Hayward, Matthew W.; Aal, Konstantin; Heuer, Marcus; Tomeletso, Mathata; Wulf, Volker; Somers, Michael J.; Stein, Andrew B. (Frontiers in Ecology and Evolution, 2019)
Across Africa, lions (Panthera leo) are heavily persecuted in anthropogenic landscapes. Trans-disciplinary research and virtual boundaries (geofences) programmed into GPS-tracking transmitters offer new opportunities to improve coexistence. During a 24-month pilot study (2016-2018), we alerted communities about approaching lions, issuing 1,017 alerts to four villages and 19 cattle posts. Alerts reflected geofence breaches of nine lions (2,941 monitoring days) moving between Botswana’s Okavango Delta and adjacent agro-pastoral communities. Daily alert system costs per lion were US18.54, or 5,460.24 per GPS deployment (n = 13). Alert-responsive livestock owners mainly responded by night-kraaling of cattle (68.9%), significantly reducing their losses (by 124.61 annually), whereas losses of control group and non-responsive livestock owners remained high (317.93 annually). Community satisfaction with alerts (91.8%) was higher than for compensation of losses (24.3%). Study lions spent 26.3% of time monitored in geofenced community areas, but accounted for 31.0% of conflict. Manual alert distribution proved challenging, static geofences did not appropriately reflect human safety or the environment’s strong seasonality that influenced cattle predation risk, and tracking units with on-board alert functions often failed or under-recorded geofence breaches by 27.9%. These insufficiencies prompted the design of a versatile and autonomous lion alert platform with automated, dynamic geofencing. We co-designed this prototype platform with community input, thereby incorporating user feedback. We outline a flexible approach that recognizes conflict complexity and user community heterogeneity. Here, we describe the evolution of an innovative Information and Communication Technologies-based alert system that enables instant data processing and community participation through interactive interfaces on different devices. We highlight the importance of a trans-disciplinary co-design and development process focussing on community engagement while synthesising expertise from ethnography, ecology, and socio-informatics. We discuss the bio-geographic, social, and technological variables that influence alert system efficacy and outline opportunities for wider application in promoting coexistence and conservation.